Codanin-1 mutations in congenital dyserythropoietic anemia type 1 affect HP1 alpha localization in erythroblasts - Renella, R; Roberts, N; Brown, J; De Gobbi, M; Bird, L; Hassanali, T; Sharpe, J; Sloane-Stanley, J; Ferguson, D; Cordell, J; Buckle, V; Higgs, D; et al. (2011)
Congenital dyserythropoietic anemia type 1 (CDA-1), a rare inborn anemia characterized by abnormal chromatin ultrastructure in erythroblasts, is caused by abnormalities in codanin-1, a highly conserved protein of unknown function. We have produced 3 monoclonal antibodies to codanin-1 that demonstrate its distribution in both nucleus and cytoplasm by immunofluorescence and allow quantitative measurements of patient and normal material byWestern blot.Adetailed analysis of chromatin structure in CDA-1 erythroblasts shows no abnormalities in overall histone composition, and the genomewide epigenetic landscape of several histone modifications is maintained. However, immunofluorescence analysis of intermediate erythroblasts from patients with CDA-1 reveals abnormal accumulation of HP1α in the Golgi apparatus. A link between mutant codanin-1 and the aberrant localization of HP1α is supported by the finding that codanin-1 can be coimmunoprecipitated by anti-HP1α antibodies. Furthermore, we show colocalization of codanin-1 with Sec23B, the protein defective in CDA-2 suggesting that the CDAs might be linked at the molecular level. Mice containing a gene-trapped Cdan1 locus demonstrate its widespread expression during development. Cdan1gt/gt homozygotes die in utero before the onset of primitive erythropoiesis, suggesting that Cdan1 has other critical roles during embryogenesis. © 2011 by The American Society of Hematology.